2020
DOI: 10.3390/ijerph17113892
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Prescribing Patterns of Metamizole in Germany Based on Data from 70 Million Persons

Abstract: The non-opioid analgesic metamizole (dipyrone) is commonly used in Germany despite its narrow indications and market withdrawal from several countries. In this study we analyzed prescribing patterns of metamizole focusing on regional differences. The source of data was the “Information system for health care data” which includes data from the statutory health insurance funds for about 70 million Germans. We received aggregated data of individuals with at least one metamizole prescription in 2010 as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
3
12
0
2
Order By: Relevance
“…They are currently not included in the list of essential medicines [ 33 ]. Some studies have shown that the frequency of use and prescription patterns of analgesics vary according to the geographical area of each country [ 34 36 ], which was also seen in this report. No published studies comparing the prescription patterns for analgesics between a country’s capital cities and municipalities were found; however, in Germany, Hoffmann et al .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…They are currently not included in the list of essential medicines [ 33 ]. Some studies have shown that the frequency of use and prescription patterns of analgesics vary according to the geographical area of each country [ 34 36 ], which was also seen in this report. No published studies comparing the prescription patterns for analgesics between a country’s capital cities and municipalities were found; however, in Germany, Hoffmann et al .…”
Section: Discussionsupporting
confidence: 80%
“…They are currently not included in the list of essential medicines [33]. Some studies have shown that the frequency of use and prescription patterns of analgesics vary according to the geographical area of each country [34][35][36], which was also seen in this report.…”
Section: Discussionsupporting
confidence: 62%
“…Previous analyses on regional variations in drug use in Germany in particular on a state level are scarce (Müller-Nordhorn et al , 2005; Kern et al , 2006; Windt, Glaeske and Hoffmann, 2013). A recent study that equally to our study was based on the DIMDI data showed east-west differences in prescribing patterns of metamizole (Hoffmann et al , 2020) similar to our results for an antidepressant. Nevertheless, observed east-west disparities depend on the kind of drug class that was considered.…”
Section: Discussionsupporting
confidence: 90%
“…Míra analgetického účinku umísťuje metamizol do prvního stupně WHO analgetického žebříčku (10). Při jednorázovém nebo krátkodobém podávání u akutní bolesti je účinnost metamizolu srovnatelná nebo vyšší než účinnost paracetamolu a kyseliny acetylsalicylové ve stejných dávkách (11)(12)(13)(14)(15)(16).…”
Section: Metamizol (Dipyron)unclassified